Representasi Relief Ogung (Gong) pada Kubur Kuna Situs Sutan Nasinok Harahap, Kecamatan Batang Onang, Kabupaten Padang Lawas Utara, Sumatera Utara - Nenggih Susilowati (Balai Arkeologi Sumatera Utara, 2017)
AbstractGong musical instrument as an ornamental motif is found on ancient graves at Sutan Nasinok Harahap Site, Batang Onang Subdistrict, North Padang Lawas Regency, in North Sumatera Province. Sutan Nasinok Harahap site is an ancient grave complex located on a quite extensive landscape of about ± 7 Ha. The purpose is to find out the reasons for the use of gong decorative motifs and interpret the use of gong decorative motifs on the ancient graves at the site.The applied method is qualitative research with ethno-archaeology study. The study was used to interpret more deeply the ogung (gong) relief at the ancient grave site of Sutan Nasinok Harahap. Comparison with existing ethnographic data is expected to give a good picture about the meaning of ogung (gong) relief on ancient grave complex at Sutan Nasinok Harahap Site. The result shows that ogung (gong) relief on the ancient grave complex of Sutan Nasinok Harahap Site confirms the long journey of utilization of the instrument from the past until now. Its position on the tombs in particular also reveals that the figures who have been buried had carried out customary duties such as horjagodang during their lives – namely Siriaon (joyous event), Sipareon (to raise dignity), and even on the occasion of death or Siluluton (sad event) – carried out by their heirs. The existence of ogung (gong) reliefs and the like can also illustrate that the buried figure is a distinguished figure and had been given the title of adat king. AbstrakAlat musik gong sebagai motif hias terdapat pada kubur kuna di Situs Sutan Nasinok Harahap,Kecamatan Batang Onang, Kabupaten Padang Lawas Utara, Provinsi Sumatera Utara. Situs Sutan Nasinok Harahap merupakan kompleks kubur kuna yang terletak pada bentang lahan yang cukup luas sekitar ±7 Ha. Adapun tujuannya adalah mengetahui alasan pemanfaatan motif hias gong dan memaknai pemanfaatan motif hias gong pada kubur kuna di situs itu. Metode yang diterapkan adalah penelitian kualitatif dengan kajian etnoarkeologi. Kajian itu dimanfaatkan untuk memaknai lebih dalam tentang relief ogung (gong) di kompleks kubur kuna Situs Sutan Nasinok Harahap. Perbandingan dengan data etnografi yang ada, diharapkan dapat memberikan gambaran yang baik tentang makna relief ogung (gong) pada kompleks kubur kuna di Situs Sutan Nasinok Harahap. Hasilnya relief ogung (gong) di kompleks kubur kuna Situs Sutan Nasinok Harahap menjadi bukti perjalanan panjang pemanfaatan alat musik tersebut dari dahulu hingga kini. Posisinya pada bangunan kubur secara khusus dapat dimaknai bahwa tokoh yang dikuburkan telah melaksanakan kewajiban adat seperti horja godang semasa hidup (Siriaon/suka cita), Sipareon (penaik harkat martabat), dan bahkan saat kematian (Siluluton/duka cita) yang dilaksanakan oleh ahli warisnya. Keberadaan relief ogung (gong) dan sejenisnya juga dapat menggambarkan bahwa tokoh yang dikuburkan adalah tokoh terhormat dan telah mendapat gelar raja adat.